Generalized Bessel potentials on Lipschitz type spaces - Iaffei, Bibiana Raquel (2005)
We introduce generalizations of Bessel potentials by considering operators of the form ℓ [(I - Δ) -1/2] where the functions ℓ extend the classical power case. The kernel of such an operator is subordinate to a growth function η. We explore conditions on η in such a way that these operators become isomorphisms between generalized Lipschitz spaces.